Relationships between physical and chemical characteristics and calculated metabolizable energy values in barley and oats with highly variable volume weights - Salo, Maija-Liisa (Agricultural and Food Science, 1978)
61 samples of barley with a volume weight of 38—75 kg/hl, and 49 oat samples with a volume weight of 40—65kg/hl were analyzed for physical and chemical characteristics. The approximate metabolizable energy (ME) value was calculated from the composition. The physical characteristics varied more, but the starch content less, in barley than in oats. There was also a negative correlation between starch and crude protein, and ether extract level in barley, but not in oats. Therefore the difference between the ME values of the best and the poorest samples was only 12% for barley, but 27 % for oats. Both the starch and the crude protein content predicted the ME value well: R2 of starch was 78—94 %, and that of crude fibre 55—84 %. The volume weight still gave a good indication for barley, but not at all for oats.